Dosimetric selection for helical tomotherapy based stereotactic ablative radiotherapy for early-stage non-small cell lung cancer or lung metastases. - Alexander Chi (Public Library of Science (PLoS), 2012)
Background No selection criteria for helical tomotherapy (HT) based stereotactic ablative radiotherapy (SABR) to treat early stage non-small cell lung cancer (NSCLC) or solitary lung metastases has been established. In this study, we investigate the dosimetric selection criteria for HT based SABR delivering 70 Gy in 10 fractions to avoid severe toxicity in the treatment of centrally located lesions when adequate target dose coverage is desired. Materials and methods 78 HT-SABR plans for solitary lung lesions were created to prescribe 70 Gy in 10 fractions to the planning target volume (PTV). The PTV was set to have ≥95% PTV receiving 70 Gy in each case. The cases for which dose constraints for ≥1 OAR could not be met without compromising the target dose coverage were compared with cases for which all target and OAR dose constraints were met. Results There were 23 central lesions for which OAR dose constraints could not be met without compromising PTV dose coverage. Comparing to cases for which optimal HT-based SABR plans were generated, they were associated with larger tumor size (5.72±1.96 cm vs. 3.74±1.49 cm, p<0.0001), higher lung dose, increased number of immediately adjacent OARs ( 3.45±1.34 vs. 1.66±0.81, p<0.0001), and shorter distance to the closest OARs (GTV: 0.26±0.22 cm vs. 0.88±0.54 cm, p<0.0001; PTV 0.19±0.18 cm vs. 0.48±0.36 cm, p = 0.0001). Conclusion Delivery of 70 Gy in 10 fractions with HT to meet all the given OAR and PTV dose constraints are most likely when the following parameters are met: lung lesions ≤3.78 cm (11.98 cc), ≤2 immediately adjacent OARs which are ≥0.45 cm from the gross lesion and ≥0.21 cm from the PTV.